Tinjauan Yuridis Proses Pengangkatan Anak (Adopsi) Di Yayasan Pemeliharaan Anak Dan Bayi (Ypab) Permata Hati Surakarta - Yuliati, Ratna; , Darsono, S.H., M.Hum; , Mutimatun Ni'ami, S.H., M.Hum (2016)
This study aims to determine the process of adoption (adoption) carried out by the prospective adoptive parents at the Child and Infant Care Foundation (YPAB) Permata Hati Surakarta and the impact after the adoption of the adopted child. The method used is the juridical law sociological research methods. This type of research is descriptive research. From the research process of adoption at the Child and Infant Care Foundation (YPAB) Permata Hati Surakarta guided by the Minister of Social Affairs Regulation No. 110/Huk/2009 on Adoption Requirements. The conclusion of this study compatibility between the process of adoption in the Child and Infant Care Foundation (YPAB) Permata Hati Surakarta with Minister of Social Affairs Regulation No. 110/Huk/2009 on Adoption Requirements. The legal consequences arising after the adoption of the adopted child is due to the inheritance law and the legal consequences of the guardianship